Improving Recovery of Irritant Hand Dermatitis in Healthcare Workers With Workplace Interventions During the COVID-19 Pandemic - Loi, Alicia S. T.; Aribou, Zeenathnisa M.; Fong, Yuke Tien (Frontiers in Public Health, 2022)
Introduction: Occupational hand dermatitis is common among healthcare workers, with increased incidence during the COVID-19 pandemic. Irritant contact dermatitis accounts for the majority of occupational hand dermatitis and is largely due to frequent contact with hand hygiene products. Long-term prognosis of occupational contact dermatitis is often very poor. This study aims to identify and implement suitable workplace interventions to aid in the recovery of occupational irritant hand dermatitis among healthcare workers during the COVID-19 pandemic. Methods A quality improvement (QI) project was performed in a tertiary hospital using the Plan-Do-Study-Act model. Healthcare workers seen at the Occupational Dermatology Clinic from March 2020 to May 2021 for the first time for likely occupational irritant dermatitis were targeted for the project. Four workplace interventions were implemented: (a) substitute current alcohol-based hand rub (ABHR) with a different, gentler ABHR, (b) alternate ABHR with gentle hand wash products, (c) temporary job modification with less clinical work (d) switch latex gloves to nitrile gloves. The improvement was assessed after 2 months of workplace intervention using a visual analogue scale, based on changes seen on photographs taken at the baseline and monthly review. The target improvement was set at 70% after 2 months of workplace interventions. Results A total of 21 participants were included in the QI project. All participants were found to have significant improvement in their hand condition. The estimated mean reduction of signs and symptoms was 80% in comparison to their baseline hand condition before intervention. Conclusion Workplace interventions such as substituting irritant hand hygiene products with gentler alternatives and temporary reduction in clinical duties may be useful in improving the recovery rate of irritant hand dermatitis among healthcare workers. Areas with high hand hygiene workload or high incidences of hand dermatitis may opt to implement systemic workplace changes.